A Atractylodes lancea polysaccharide inhibits metastasis of human osteosarcoma U‐2 OS cells by blocking sialyl Lewis X (sLex)/E‐selectin binding. Issue 21 (28th September 2020) - Zhong, Kaihua; Fan, Shuxin; Yao, Shujun; Xu, Haibin; Bai, Suping
Abstract: In this study, a new water and alkaline‐soluble polysaccharide (ALP), with an average molecular weight of 6.63 × 10 4  Da, was successfully purified from the rhizomes of Atractylodes lancea . GC analysis demonstrated that ALP was a kind of glucan. The effect of the ALP on the interaction between E‐selectin and sialyl Lewis X (sLe x ) was examined in human osteosarcoma U‐2 OS cells. It was obvious that the expression of sLe x antigen on the surface of U‐2 OS cells was visible under fluorescence microscopy. The addition of ALP (0.5, 1 and 2 mg/mL) resulted in a marked inhibition on the adhesion, migration and invasion of U‐2 OS cells to human umbilical vein endothelial cells (HUVECs), which was achieved by the decreased sLe x expression on U‐2 OS cells. Additionally, the induction of apoptosis can be observed in U‐2 OS cells following ALP treatment using TUNEL staining and Annexin V‐FITC/PI double‐staining analysis on flow cytometry. In conclusion, these results indicated that ALP exerted anti‐metastatic activity towards osteosarcoma cells via inhibition of sLe x /E‐selectin binding, which suggested that ALP could be a potent agent for human osteosarcoma intervention.